MEDICAL AND SOCIAL ASPECTS OF THE FORMATION OF REPRODUCTIVE HEALTH OF ADOLESCENTS (International journal of medical sciences, 2026)
This review article examines the medical and social aspects of adolescent reproductive health development from the perspective of public health and preventive medicine. It analyzes current data on the influence of biological, socioeconomic, behavioral, and psychoemotional factors on the development of reproductive function during adolescence. Particular attention is paid to sex education, access to health care, the prevalence of early sexual intercourse, sexually transmitted infections, and risk factors for reproductive health problems. Research findings reflecting the role of family, educational environment, and social conditions in shaping adolescent attitudes and behavior are summarized. The need for comprehensive preventive programs aimed at strengthening reproductive health and reducing medical and social risks in the adolescent population is emphasized.